Development of real-time investigation technique for nonpoint pollution source distribution using programming interface - Min, Kwan Sik; Lee, Dong Ha; Acharya, Tri Dev (Journal of Environmental Engineering and Landscape Management, 2019)
Currently both central and local governments that are aware of the importance of conserving rivers, are making continuous efforts to solve the problem of non-point pollution sources (NPS) flowing into rivers. This study established a reactive web service app with a mobile application, to accommodate the need for systematic and scientific investigation and management of NPS. The developed investigation and management techniques incorporate all the PC-based administrative features, thereby improving development efficiency. A prototype of mobile GIS platform for a survey, inspection, and input was proposed, in which data related to pollution source locations and attributes can be effectively collected, stored, updated, and adjusted. To demonstrate, we conducted a quantitative analysis of river pollution source using GPS and GIS to show further details of the framework, which provides geographic information required to develop management technique of NPS flowing into rivers and related parameters in the form of a map. Furthermore, based on the interpolated maps and various environmental factors, the prediction of NPS as well as other parameters can be done. The research will not only improve the efficiency of investigation and management of NPS but also contribute to establishing a management policy, which covers quick decision-making and reaction to inflow accidents.